The electronic excited states of dichloromethane in the 5.8-10.8 eV energy range investigated by experimental and theoretical methods. (September 2020) - Lange, E.; Jones, N.C.; Hoffmann, S.V.; Lozano, A.I.; Kumar, S.; Homem, M.G.P.; Śmiałek, M.A.; Duflot, D.; Brunger, M.J.; Limão-Vieira, P.
Highlights: We have presented a comprehensive investigation of the VUV electronic-state spectroscopy of dichloromethane in the 5.8–10.8 eV energy range, with the most reliable and complete set of absolute photoabsorption cross-sections for this region being given. The main absorption features are due to electronic excitations from the ground state to valence, Rydberg and mixed-character states. Novel assignments have been made, which have not been previously reported in the literature. Theoretical calculations on the vertical excitation energies and oscillator strengths were performed using the equation-of-motion coupled cluster method. Potential energy curves as a function of the C–Cl coordinate, for the four lowest-lying excited A′ and A″ states, were calculated at the EOM-CCSD level of theory with aug-cc-pV5Z(g)+R basis set. Abstract: We present a comprehensive experimental high-resolution vacuum ultraviolet (VUV) photoabsorption spectrum of dichloromethane, CH2 Cl2, with absolute cross sections determined for the full 5.8–10.8 eV energy-range. The calculations on the vertical excitation energies and oscillator strengths were performed using the equation-of-motion coupled cluster method, restricted to the single and double excitations level (EOM-CCSD), and were used to help analyse the valence and Rydberg structures in the photoabsorption spectrum. The present spectrum additionally reveals several new features not previously reported in the literature, with particular reference to the valence σ C C l * ( 10 a 1 ) ← n C l ( 7 b 2 ) ( 1 1 B 2 ← X ˜ 1 A 1 ) and ( σ C C l * ( 10 a 1 ) ← n C l ( 9 a 1 ) + σ C H * ( 11 a 1 ) ← n C l ( 7 b 2 ) ) ( 1 1 A 1 ← X ˜ 1 A 1 ) transitions at 7.519 and 7.793 eV. A vibrational progression of the CCl2 symmetric stretching, ν 3 ′, and CCl2 scissoring, v 4 ′ ( a 1 ), modes have also been assigned for the first time in the 7.4–8.6 eV energy range. The measured absolute photoabsorption cross sections have been used to calculate the photolysis lifetime of dichloromethane in the Earth's atmosphere (0–50 km). Potential energy curves as a function of the C–Cl coordinate, for the four lowest-lying excited A′ and A″ electronic states, have additionally been calculated at the EOM-CCSD level of theory.